2009
DOI: 10.2319/062008-322.1
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Evaluation of Octenidine Dihydrochloride Mouth Rinse after 5 Days' Use in Orthodontic Patients

Abstract: Objective: To determine the absolute and relative antibacterial activity of octenidine dihydrochloride (OCT) against total and cariogenic bacteria in saliva samples of patients with fixed orthodontic appliances during 5 days of usage. Materials and Methods: The study group consisted of 5 male and 13 female subjects who were selected from patients in the Clinic of Orthodontics. Each patient was given physiologic saline (PS), chlorhexidine gluconate (CHX), polyvinylpyrrolidone-iodine complex (PVP-I), and OCT eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Streptococcus mutans and Lactobacilli are known as most closely bacteria associated with dental caries ( 9 - 11 ). Shortly after bonding orthodontic attachments, level of these bacteria in the oral cavity elevates due to plaque accumulation ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptococcus mutans and Lactobacilli are known as most closely bacteria associated with dental caries ( 9 - 11 ). Shortly after bonding orthodontic attachments, level of these bacteria in the oral cavity elevates due to plaque accumulation ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Shortly after bonding orthodontic attachments, level of these bacteria in the oral cavity elevates due to plaque accumulation ( 12 , 13 ). Reduction of these cariogenic bacteria is an important step to prevent caries ( 11 ). It has been shown that chlorhexidine (CHX) and fluoride mouthrinses have activity against oral pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…prior to operations, for plaque reduction, in ventilated patients and to eradicate a colonization with MRSA) [1] . OPE as well as octenidine alone were significantly superior to other current oral cavity antiseptics [38][39][40] . OPE showed expressed antimicrobial action in the regime of anti-inflammatory therapy of parodontal diseases [41] .…”
Section: Genitaliamentioning
confidence: 99%
“…However, data from in vitro and in vivo studies suggest that mouthrinses containing Octeneidine hydrochloride as an active ingredient had comparable [72] or greater effectiveness than CHX on cariogenic bacteria. [73][74][75] Further, a recent 4-day plaque-regrowth study found that Octeneidine had antibacterial and antiplaque efficacy comparable to CHX. In spite of the promising findings, this molecule has not been widely used which might be due to its bitter taste and also partly due to the lack of evidence from studies with longer follow-up periods.…”
Section: Octeneidinementioning
confidence: 99%